2016
DOI: 10.1038/srep37821
|View full text |Cite
|
Sign up to set email alerts
|

Long intergenic non-coding RNA expression signature in human breast cancer

Abstract: Breast cancer is a complex disease, characterized by gene deregulation. There is less systematic investigation of the capacity of long intergenic non-coding RNAs (lincRNAs) as biomarkers associated with breast cancer pathogenesis or several clinicopathological variables including receptor status and patient survival. We designed a two-stage study, including 1,000 breast tumor RNA-seq data from The Cancer Genome Atlas (TCGA) as the discovery stage, and RNA-seq data of matched tumor and adjacent normal tissue fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 63 publications
2
26
0
Order By: Relevance
“…These three lncRNAs-based signature could facilitate the prognosis prediction of esophageal squamous cell carcinoma. Moreover, Zhang et al also found that LINC01614 was highly expression in ER positive BRCA which was in line with our result (Zhang et al 2016b). These findings highlighted the potential role of LINC01614 in BRCA and it might be an useful biomarker for BRCA prognostic prediction.…”
Section: Discussionsupporting
confidence: 91%
“…These three lncRNAs-based signature could facilitate the prognosis prediction of esophageal squamous cell carcinoma. Moreover, Zhang et al also found that LINC01614 was highly expression in ER positive BRCA which was in line with our result (Zhang et al 2016b). These findings highlighted the potential role of LINC01614 in BRCA and it might be an useful biomarker for BRCA prognostic prediction.…”
Section: Discussionsupporting
confidence: 91%
“…Increasing data had shown that lncRNAs could regulate gene expression both at transcriptional and post-transcriptional levels, including the regulation of splicing, mRNA processing, and translation [ 55 ]. It had been demonstrated that some lncRNAs implicated in breast normal development and cancer based on their expression pattern, function and localization in human and mouse [ 56 , 57 ]. However, limited researches had been reported the regulation mechanism of lncRNAs on bovine lactation.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, DRAIC expression was identified as a potential onco-lncRNA based on its elevated expression in tumor tissues compared to the adjacent normal tissues [23]. It was shown to be higher in ER positive breast cancer patients from 4 different studies [23,24,25,26].…”
Section: Discussionmentioning
confidence: 99%